Relative severity of aflatoxin contamination of cereal crops in West Africa - Bandyopadhyay, Ranajit; Kumar, M.; Leslie, J. (Informa UK Limited, 2007)
Aflatoxins are a common contaminant of cereals that can cause cancer, liver disease, immune suppression, retarded growth and development, and death, depending on the level and duration of exposure. Maize is an introduced crop to Africa and there have been efforts over the last 20 years or so to replace traditional cereal crops, such as sorghum (Sorghum bicolor) and pearl millet (Pennisetum glaucum), with maize. We found that maize was significantly more heavily colonized by aflatoxin-producing Aspergillus spp. than either sorghum or millet, with overall aflatoxin levels being correspondingly higher. On average, Nigerians consume 138 kg cereals annually. If the primary cereal is sorghum instead of maize, then the risk of aflatoxin-related problems is reduced 4-fold; if it is pearl millet, then the risks are reduced 8-fold. Development programs and other ventures to increase maize production in marginal cropping areas of Africa should be reconsidered and, instead, efforts to improve/maintain traditional crops encouraged.